Comparison between platelet rich fibrin as space filling material versus xenograft and alloplastic bone grafting materials in immediate implant placement: a randomized clinical trial - Heba Abo-Elfetouh Elsheikh; Sally Elsayed Abdelsameaa; Ahmed Adel Elbahnasi; Fakhreldin Hassan Abdel-Rahman (BMC, 2023)
Abstract Background This study aimed to compare the efficacy of different gap filling materials in immediate implant in anterior and premolar regions of maxilla. Materials and methods Thirty-six implants were inserted in patients seeking for replacement of non-restorable maxillary anterior and premolar teeth (esthetic zone) by immediate implant. Patients were randomly distributed into three equal groups, twelve implants in each group. Group 1 received Platelet Rich Fibrin (PRF) into the jumping distance, Group 2 received Xenograft into the jumping distance and Group 3 received Alloplastic bone grafting material into the jumping distance. Implant stability by measuring the changes in Resonance Frequency Analysis (RFA), peri-implant pocket depth, marginal bone loss and changes in buccal bone thickness were evaluated during follow up periods. All the clinical and radiographic data were subjected to statistical analysis by One Way ANOVA test and the Post Hoc Tukey test. Results This study involved 19 female patients and 17 male patients who received 36 dental implants. There was no significant difference between the study groups regarding implant stability, peri-implant pocket depth and palatal bone loss, while there was a significant difference between PRF Group (Group 1) and the other Groups regarding buccal bone loss and changes in buccal bone thickness. Conclusion PRF can be used as a gap filling material in conjunction with immediate implant placement, but other bone grafting materials give superior result regarding buccal bone loss and changes in buccal bone thickness. Trial registration The study was listed on www.clinicaltrials.gov with registration number (NCT05878392) on 26/05/2023. The Institutional Review Board (IRB) of the Faculty of Dentistry, Mansoura University, Mansoura, Egypt, approved the current study in compliance with the seventh revision of the Helsinki Declaration in 2013 (A0103023OS).